WRESTLING WITH MANHOOD: EXPRESSIONS OF MASCULINITY IN BALKAN OILED WRESTLING (ЕтноАнтропоЗум, 2015)
Wrestling in many cultures is considered an essential expression of manhood and masculinity. However, recent research in gender studies has problematized the notion of masculinity, suggesting that it has several different faces. Through examining the philosophies, representations and practices surrounding male wrestling in general and the sport of oiled Pelivan wrestling in Macedonia, this paper seeks to not only illustrate differing notions of masculinity but to show how they are expressed and played out in the context of this traditional form of wrestling.